2021
DOI: 10.1155/2021/1840915
|View full text |Cite|
|
Sign up to set email alerts
|

Combination of Traditional Chinese and Western Medicine in Sports in Pharmaceutical Health

Abstract: The health problems caused by insufficient exercise are becoming more and more serious, which is a serious threat to human health, especially the increase in patients with chronic diseases, which brings a heavy burden to medical and health care, and even triggers a public health crisis. In order to cope with the health threats people face, how to promote the synergistic effect of sports and medical health under the background of the integration of Chinese and Western medicine has become an important issue in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The game study of shuttlecock is the development of shuttlecock based on game theory and it is a comprehensive research result. Shuttlecock requires not only content inheritance, technology inheritance, and spirit inheritance but also inheritance scope and level [ 14 ]. The integration of sports shuttlecock inheritance and other cultures requires mastering the corresponding development trends and the current development of the game decision model, as shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The game study of shuttlecock is the development of shuttlecock based on game theory and it is a comprehensive research result. Shuttlecock requires not only content inheritance, technology inheritance, and spirit inheritance but also inheritance scope and level [ 14 ]. The integration of sports shuttlecock inheritance and other cultures requires mastering the corresponding development trends and the current development of the game decision model, as shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%